Drug-induced Acute Kidney Injury: A Clinico-etiological Study from a Tertiary Care Center in Northeast India - Manjuri Sharma; Faheem Nazir Qanoongo; Prodip Kumar Doley; Gayatri Pegu; Miranda Pegu (Journal of Nature and Science of Medicine)
Background Drug-induced acute kidney injury (AKI) poses a significant challenge in clinical practice, necessitating a comprehensive understanding of its epidemiology and underlying mechanisms. This prospective study aimed to elucidate the clinico-etiological profile of drug-induced AKI in a tertiary care center in Northeast India and evaluate patient outcomes. Methodology Adults diagnosed with AKI following drug exposure were enrolled in this observational study conducted from August 2022 to January 2024 at Department of Nephrology, Gauhati Medical College and Hospital. Demographic data, clinical characteristics, offending pharmaceutical agents, histopathological patterns, and outcomes were meticulously documented. Results We studied 105 participants (mean age: 45 ± 10 years, 56.2% male) experiencing drug-induced AKI. Antimicrobials (24%), nonsteroidal anti-inflammatory drugs (NSAIDs) (21%), and chemotherapeutic agents (19%) were common causes, leading predominantly to acute interstitial nephritis (58%) and renal tubular epithelial cell injury (30%). Despite challenges, 73% fully recovered, with a 2% mortality rate. Age (odds ratio [OR]: 1.35, 95% confidence interval [CI]: 1.12–1.63, P = 0.002), male gender (OR: 1.84, 95% CI: 1.09–3.11, P = 0.022), diabetes (OR: 2.21, 95% CI: 1.28–3.82, P = 0.005), smoking (OR: 1.92, 95% CI: 1.06–3.48, P = 0.031), antimicrobial use (OR: 3.68, 95% CI: 2.14–6.32, P < 0.001), NSAID use (OR: 2.77, 95% CI: 1.56–4.92, P < 0.001), and chemotherapeutic use (OR: 1.57, 95% CI: 1.10–2.22, P < 0.001) were significant risk factors. Conclusion This study highlights the clinico-etiological profile of drug-induced AKI in Northeast India, emphasizing antimicrobials, NSAIDs, and chemotherapeutics as major contributors. Despite the high prevalence, most patients recovered, stressing early recognition and careful medication management. Age, gender, and comorbidities play critical roles, warranting targeted interventions and vigilant pharmacovigilance to mitigate the AKI burden effectively.